1976
DOI: 10.1136/gut.17.11.888
|View full text |Cite
|
Sign up to set email alerts
|

Tropical enteropathy in Rhodesia.

Abstract: SUMMARY Tropical enteropathy, which may be related to tropical sprue, has been described in many developing countries including parts of Africa. The jejunal changes of enteropathy are seen in Rhodesians of all social and racial categories. Xylose excretion, however, is related to socioeconomic status, but not race. Upper socioeconomic Africans and Europeans excrete significantly more xylose than lower socioeconomic Africans. Vitamin B12 and fat absorption are normal, suggesting predominant involvement of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13] A previous study in Zimbabwe found that individuals of a lower economic status excreted significantly less xylose, a measure of intestinal absorption, than those individuals of a higher economic status. 18 A more recent study in rural Bangladesh found that children residing in "contaminated" environments *Address correspondence to Christine Marie George, Department of International Health, Johns Hopkins University, 615 N. Wolfe Street, Room E5535, Baltimore, MD 21205-2103. E-mail: cmgeorge@jhsph.edu defined by water quality, improved sanitation, and hygiene conditions had significantly higher L:M ratios in urine compared with children in "clean" environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13] A previous study in Zimbabwe found that individuals of a lower economic status excreted significantly less xylose, a measure of intestinal absorption, than those individuals of a higher economic status. 18 A more recent study in rural Bangladesh found that children residing in "contaminated" environments *Address correspondence to Christine Marie George, Department of International Health, Johns Hopkins University, 615 N. Wolfe Street, Room E5535, Baltimore, MD 21205-2103. E-mail: cmgeorge@jhsph.edu defined by water quality, improved sanitation, and hygiene conditions had significantly higher L:M ratios in urine compared with children in "clean" environments.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,14 EE is thought to arise from unsanitary environmental conditions that lead to repeated exposure to enteric pathogen causing chronic infections. [15][16][17][18] There is a growing body of literature suggesting that these chronic enteric infections alter intestinal structure and function in a manner that is suboptimal for child growth. [7][8][9] It is suspected that many of these infections in children are subclinical and that diarrhea only accounts for a small proportion of EE.…”
Section: Introductionmentioning
confidence: 99%
“…There was a dense infiltration of lymphocytes and plasma cells in the lamina propria of every specimen; 20 were grade 3 and 11 grade 2. The histological, dissecting microscopy and cellular infiltration grades (x2) and the histological measurements (Mann Whitney U test) were all significantly inferior to a group of healthy African controls (Thomas et al, 1976) (p< 0-001). …”
Section: Histology Gradesmentioning
confidence: 78%
“…In 1968 Clain presented preliminary data on tropical Received for publication 4 August 1976 sprue in Rhodesia. We have now established the presence of subclinical tropical enteropathy in Rhodesia (Thomas et al, 1976) and in this paper describe 31 cases of tropical sprue, 28 of which had megaloblastic anaemia and the remaining three gastrointestinal complaints and weight loss.…”
mentioning
confidence: 84%
See 1 more Smart Citation